A Neuropsychiatric Prelude to Unveiling Small Cell Lung Cancer with Suspected Paraneoplastic Limbic Encephalitis: A Case Report - Jessa Letargo; X. Melody Qu; Timothy K. Nguyen; Alexander V. Louie; Sara Kuruvilla; Enxhi Kotrri (Current Oncology)
Small cell lung cancer (SCLC) is an aggressive form of lung cancer characterized by rapid growth and early metastases. As a neuroendocrine tumour, SCLC is especially notorious for various paraneoplastic syndromes, one of which is a rare neurological syndrome called paraneoplastic limbic encephalitis (PLE) that manifests with amnestic cognitive impairment and seizures. Here, we describe a case of a 53-year-old female who presented with neuropsychiatric symptoms of delusions, hallucinations, and cognitive impairment that started months prior to being diagnosed with extensive-stage SCLC. With no previous neuropsychiatric history, this raised the question of whether her presentation was related to PLE rather than a primary psychiatric condition, as initially diagnosed. Her symptoms improved with chemotherapy and radiation treatment of the underlying cancer, favouring a paraneoplastic etiology. Overall, this case underscores the importance of considering paraneoplastic syndromes in patients presenting with new neuropsychiatric symptoms, as early recognition and treatment can improve prognosis.